Human trafficking - Preble, Kathleen M. (Handbook of forensic social work, 2024)
As awareness about human trafficking has increased, so too has knowledge about the phenomenon and appropriate interventions. This chapter details theoretical underpinnings, evidenced-based knowledge, and interventions for supporting survivors of human trafficking. It offers a critical examination of interventions and how they may be applied when working with survivors. The chapter discusses the impacts of human trafficking response on communities of color and gender and sexual minorities and how these considerations may influence interactions with potential survivors. Concluding this chapter is a case study involving a survivor experiencing intimate partner–based trafficking and the ethical implications of intervention based on the social work code of ethics. A table of social work principles is provided with illustrations of evidence-based and competency-based social work actions when working with survivors of trafficking.